Toxic textile dyes accumulate in wild European eel Anguilla anguilla - Belpaire, Claude; Reyns, Tim; Geeraerts, Caroline; Van Loco, Joris (Chemosphere (Oxford), 2015)
[Display omitted] •Malachite Green and Crystal Violet, used in textile industry, are accumulating in wild freshwater fish.•Prevalence of dyes in the European eel is high in Belgium (77% of the studied sites).•Dye contaminated eel is unfit for human consumption.•Dyes accumulating in wildlife may form a global environmental problem. Dyes are used to stain inks, paints, textile, paper, leather and household products. They are omnipresent, some are toxic and may threaten our environment, especially aquatic ecosystems. The presence of residues of sixteen dyes (triarylmethanes, xanthenes, phenothiazines and phenoxazines) and their metabolites was analyzed in muscle tissue samples of individual yellow-phased European eels (Anguilla anguilla) from 91 locations in Belgian rivers, canals and lakes sampled between 2000 and 2009 using ultra performance liquid chromatography-tandem mass spectrometry. Eel was contaminated by dyes in 77% of the sites. Malachite Green, Crystal Violet and Brilliant Green were present in 25–58% of the samples. Dye occurrence was related to the distribution of textile and dye production industries. This field study is the first large-scale survey to document the occurrence of artificial dyes in wildlife. Considering the annual amounts of dyes produced worldwide and the unintentional spillage during their use, our observations warrant additional research in other parts of the world. The presence of these highly toxic dyes in the European eel may form an additional threat to this critically endangered species. The contaminated eels should be considered as not suitable for consumption.